PERLUASAN MAKNA KANJI YANG MEMILIKI BUSHU TE-HEN - Kitoko, Daeng Ilham; Aibonotika, Arza; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Kanji is one of the four characters used by Japanese people. Bushu is a form element that represents the basic meaning of a kanji. Understanding of bushu is necessary to understand a kanji. This study aimed to describes the meaning and the semantic change of te-hen Bushu. This research is limited to kanji characters containing te-hen bushu in Jouyou Kanji (daily use of kanji). The method used in this study is a qualitative method. Kanji dictionary and the book of the origin of kanji is used to find semantic change of te-hen bushu. The results of the analysis of the kanji which have bushu te-hen was found that there was an semantic change from concrete to abstract, semantic change of a specific meaning to a general, specific of a general meaning to a specific, and semantic change in a positive direction.Key Words: Kanji, Bushu, Te-Hen, Semantic Change